2022
DOI: 10.3390/ijms23031294
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Circulatory microRNAs in Major Depressive Disorder: Potential Biomarkers for Disease Prognosis

Abstract: Major depressive disorder (MDD) is a neuropsychiatric disorder, which remains challenging to diagnose and manage due to its complex endophenotype. In this aspect, circulatory microRNAs (cimiRNAs) offer great potential as biomarkers and may provide new insights for MDD diagnosis. Therefore, we systemically reviewed the literature to explore various cimiRNAs contributing to MDD diagnosis and underlying molecular pathways. A comprehensive literature survey was conducted, employing four databases from 2012 to Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 99 publications
0
19
0
Order By: Relevance
“…Fang et al [ 65 ] reported that plasma levels of miR-132 in medication-free MDD patients were 2.4-fold higher than control subjects, and that there was a positive correlation between miR-132 levels and the severity of depression, suggesting that blood levels of miR-132-5p may be a state biomarker for depression. A recent systematic review showed a list of dysregulated circulatory miRNAs in MDD patients as the most prominent miRNAs such as miR-24-3p, miR-26a-5p, miR-135a, miR-425-3p, miR-132, miR-124, and miR-16-5p [ 50 ]. In addition, miR-132 is the most frequently upregulated miRNA in MDD patients [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fang et al [ 65 ] reported that plasma levels of miR-132 in medication-free MDD patients were 2.4-fold higher than control subjects, and that there was a positive correlation between miR-132 levels and the severity of depression, suggesting that blood levels of miR-132-5p may be a state biomarker for depression. A recent systematic review showed a list of dysregulated circulatory miRNAs in MDD patients as the most prominent miRNAs such as miR-24-3p, miR-26a-5p, miR-135a, miR-425-3p, miR-132, miR-124, and miR-16-5p [ 50 ]. In addition, miR-132 is the most frequently upregulated miRNA in MDD patients [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that miRNAs are detected in the brain and body fluids of human. Interestingly, blood levels of miRNAs in patients with MDD are altered compared to healthy control subjects [ 49 , 50 ]. Thus, it is likely that circulatory miRNAs may be potential diagnostic and therapeutic biomarkers for depression.…”
Section: Introductionmentioning
confidence: 99%
“…mir-16-5p can be upregulated by deposited Aβ in AD and induces neuronal injury and apoptosis of neuronal cells by directly targeting and repressing the expression of related genes (Kim et al, 2020). Furthermore, mir-16-5p has been identi ed as a potential marker of MDD (Rasheed et al, 2022). mir-1-3p played an important role in the regulation of tumor associated genes, and no studies have yet identi ed its role in the regulation of AD and MDD related genes.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, blood miRNA levels were shown to largely correlate with brain expression [ 55 ]. Indeed, miRNA circulating levels are a promising field of investigation [ 56 - 60 ]. Access to cerebrospinal fluid could reduce this bias [ 61 , 62 ], however feasibility is obviously a strong limitation.…”
Section: Potential Limitations Of Biomarkersmentioning
confidence: 99%